Individual characteristics and behavior in repeated games: An experimental study - Douglas Davis; Asen Ivanov; Oleg Korenok (Queen Mary University of London, School of Economics and Finance, 2014)
Using a laboratory experiment, we investigate whether a variety of behaviors in repeated games are related to an array of individual characteristics that are popular in economics: risk attitude, time preference, trust, trustworthiness, altruism, strategic skills in one-shot matrix games, compliance with first-order stochastic dominance, ability to plan ahead, and gender. We do find some systematic relationships. A subject's patience, gender, altruism, and compliance with first-order stochastic dominance have some limited systematic effects on her behavior in repeated games. At the level of a pair of subjects who are playing a repeated game, each subject's patience, gender, and ability to choose an available dominant strategy in a one-shot matrix game systematically affect the frequency of the cooperate-cooperate outcome. However, overall, the number of systematic relationships is surprisingly small.
Keywords: C91; C92; D03; D70; 330; Experiment; Repeated game; Individual characteristics